SPORA (Speaking For Academic): Cloud-Based Web to Enhance English Speaking Proficiency In Higher Education - Herdina, Griselda Gian Heris; Aini, Nurul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This article investigates and proposes a conceptual design for developing a cloud-based web platform to enhance the English proficiency learning of higher education students. Cloud-based web tools can help students overcome barriers such as a lack of practice opportunities, speaking anxiety, and less intensive feedback. There are many offerings of MALL (Mobile Assisted Language Learning) as a medium to help students develop their speaking skills. However, there is still a lack of MALL offerings for speaking learning in the form of cloud-based web applications, which limits students' access. This is because students often need to install the application first or use applications that can only be supported on a single device, such as a smartphone. Therefore, this conceptual article presents the design of SPORA (Speaking for Academic), a cloud-based web platform designed to enhance students' speaking skills through a structured and interactive digital approach. SPORA has been designed with several key features, including a space for practice questions aligned with curriculum standards, directed feedback (via chat box or two-way audio), and a CEFR (Common European Framework of Reference for Languages) standardized assessment rubric. In addition, this article also examines the potential of SPORA in technological challenges and innovations integrated with education to fulfill students' learning needs to the fullest. SPORA is presented as a cloud-based solution that opens up further research into its development and practical implementation across a range of speaking learning contexts for higher education students.